2010
DOI: 10.1007/s12185-010-0578-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of traditional methods and mitogen-stimulated direct antiglobulin test for detection of anti-red blood cell autoimmunity

Abstract: The diagnosis of autoimmune hemolytic anemia (AIHA) is based on a positive direct antiglobulin test (DAT), which is performed using various methods with different sensitivities. Recently, mitogen-stimulated (MS)-DAT was suggested to be able to identify latent anti-erythrocyte autoimmunity. Traditional methods (tube, microcolumn, and solid phase) and MS-DAT were compared in 54 consecutive cases of suspected AIHA, 28 idiopathic AIHA in clinical remission, and 12 difficult-to-diagnose cases of DAT-negative AIHA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…1,2 We describe about 5% of DAT-negative cases, a percentage rather lower than previously reported (;10% to 20% 1,2 ), possibly due to the use of more sensitive tests, such as MS-DAT, which allowed the diagnosis in some DATnegative cases. 3,4 These cases showed a more severe pattern and may represent a diagnostic puzzle, causing troublesome delays in the start of therapy. This notion is clinically important, because an earlier onset of therapy has been related with lower probability of relapse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 We describe about 5% of DAT-negative cases, a percentage rather lower than previously reported (;10% to 20% 1,2 ), possibly due to the use of more sensitive tests, such as MS-DAT, which allowed the diagnosis in some DATnegative cases. 3,4 These cases showed a more severe pattern and may represent a diagnostic puzzle, causing troublesome delays in the start of therapy. This notion is clinically important, because an earlier onset of therapy has been related with lower probability of relapse.…”
Section: Discussionmentioning
confidence: 99%
“…However, diagnostic pitfalls are recognized with increasing frequency, due to IgA autoantibodies (not detectable by most polyspecific antiglobulin reagents), warm IgM, low-affinity IgG, or IgG below the threshold of sensitivity. In fact, despite the availability of various DAT techniques (microcolumn, solid phase, enzyme linked, flow cytometry, dual DAT, and mitogen-stimulated [MS] DAT [3][4][5] ), about 10% of AIHA remains DAT negative. In these atypical cases, the diagnosis, made after extensive laboratory workup and exclusion of other causes of hemolysis, is frequently deferred, with consequent delay in therapy.…”
Section: Introductionmentioning
confidence: 99%
“…We found that 61% of HS cases showed RBC antibody-bound IgG values above the mean plus 3 SD of the controls (150 ng/mL), and one-third of positive cases values above the threshold of AIHA (250 ng/mL). [25][26][27] The presence of RBC-bound IgG in HS patients was confirmed by flow cytometry. Moreover, Western blot experiments showed binding of purified IgG to a-and b-spectrin, Band 3, and dematin.…”
Section: Discussionmentioning
confidence: 99%
“…The quantification of RBC antibodies in mitogenstimulated cultures was assessed by MS-DAT, as previously described. [25][26][27] Heparinized blood samples were diluted 1:6 with RPMI 1640 (Gibco-Life Technologies, Foster City, CA) and either unstimulated or stimulated with 2 mg/mL phytohemagglutinin (Sigma, St Louis, MO), 20 ng/mL phorbol-12-myristate-13-acetate (Sigma), and 1% pokeweed (Sigma) for 48 hours in 24-well plates. A 96-well polyvinyl chloride assay plates (Costar, Cambridge, MA) was coated with 50 mL of human IgG (Sclavo, Siena, Italy) overnight at 148C, washed 33, and blocked with 200 mL of 2% fetal calf serum-phosphate-buffered saline (PBS).…”
Section: Detection and Quantification Of Rbc Antibody-bound Igg By Msmentioning
confidence: 99%
“…Other more sophisticated techniques such as the enzyme-linked and radiolabeled tests, and the flow cytometry displayed the highest sensitivity, being able to detect up to 30 to 40 molecules of RBC autoantibodies. 3,4 Moreover, mitogen stimulation in culture, which probably amplifies the production of autoantibodies, was the most sensitive (and least specific) and has proven useful in the diagnosis of DAT-negative AIHA. 5 In addition, it was found positive in a fraction of patients with B-chronic lymphocytic leukemia or myelofibrosis without an overt diagnosis of AIHA and in more than a half of patients with hereditary spherocytosis.…”
mentioning
confidence: 99%